EMPOWERING RURAL YOUTH: A MEDIA STRATEGY FOR FOSTERING ENTREPRENEURSHIP AND TACKLING UNEMPLOYMENT - V. Sundararaman; M. Jebakumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study explores the vital role of media in shaping entrepreneurial awareness and proposes a comprehensive media strategy to bridge the gap between rural youth and entrepreneurship opportunities. In recent days, the term ’unemployment’ has become increasingly prevalent, particularly among young graduates in the Southern Districts of Tamil Nadu. The lack of employment opportunities in their hometowns has led them to migrate to urban centers like Chennai and Coimbatore. Promoting entrepreneurship awareness and knowledge is crucial for empowering rural youth to establish their ventures. This study aims to formulate a media strategy that enhances awareness and fosters an entrepreneurial mindset. The findings reveal that while rural youth have a basic awareness of entrepreneurship, there is a lack of in-depth knowledge, particularly regarding skill development and funding schemes. The study explores the media accessing patterns of rural youth, with a focus on preferred platforms such as WhatsApp and YouTube. The media strategy developed aims to leverage these platforms to disseminate entrepreneurship-related information. The study concludes by emphasizing the potential of this strategy to improve awareness, empower rural youth, and contribute to the economic growth of their communities.